Guieranone A, a naphthyl butenone from the leaves of Guiera senegalensis with antifungal activity - Silva, O (2015)
A new methoxylated naphthyl butenone, guieranone A (1), was isolated from the leaves of Guiera senegalensis. Its structure was elucidated as (2E)-1-(1,3,6,8-tetramethoxy-2-naphthyl)but-2-en-1-one, on the basis of spectroscopic data. Also isolated were two known naphthopyrones, 5-methyldihydroflavasperone (2) and 5-methylflavasperone (3). Guieranone (1) exhibited potent antifungal activity against Cladosporium cucumerinum and is the first naphthyl ketone derivative to have been isolated from the family Combretaceae.